2012
DOI: 10.1007/s13744-012-0078-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of a Castor Bean Leaf Extract and its Insecticidal Effects Against Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae)

Abstract: Keywords Euphorbiaceae, fall armyworm, pest control, plant extract, Ricinus communis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Brahim et al [25] studied the toxicity of aqueous extracts of the plant against mosquito larvae of Culex pipiens, Aedes caspius, Culiseta longiareolata and Anopheles maculipennis (Diptera: Culicidae). The leaf extract of R. communis has been shown to posses insecticidal properties against insect pests like Spodoptera frugiperda [26]; Callosobruchus chinensis [27] and Cosmopolites sordidus (Coleoptera: Curculionidae) [28]. Several studies have reported the toxic effects of various plant extracts in control of fly populations of M. domestica [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Brahim et al [25] studied the toxicity of aqueous extracts of the plant against mosquito larvae of Culex pipiens, Aedes caspius, Culiseta longiareolata and Anopheles maculipennis (Diptera: Culicidae). The leaf extract of R. communis has been shown to posses insecticidal properties against insect pests like Spodoptera frugiperda [26]; Callosobruchus chinensis [27] and Cosmopolites sordidus (Coleoptera: Curculionidae) [28]. Several studies have reported the toxic effects of various plant extracts in control of fly populations of M. domestica [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works performed with castor oil leaves suggested that trypsin inhibitor is a nonproteic organic molecule (Rossi et al, 2012) differing from other trypsin inhibitors described in literature. Precipitations with acetone and saturated ammonium solution, high temperature exposition and inhibition assays in the presence of de β-mercapto-ethanol were performed demonstrating the molecule non-proteic characteristic and suggesting different ways to extract and purify this trypsin inhibitor.…”
Section: Discussionmentioning
confidence: 76%
“…In general, percent mortality of the larvae due to insecticide application on castor had been observed to be decreased when the larvae were shifted from cotton (Figure 4e). This could be due to the fact that castor is grown as a perennial crop and S. exigua is habitual to consume it as one of the favorable hosts (Ahmad & Iqbal, 2009; Ahmad et al., 2007; Ishtiaq & Saleem, 2011; Rossi, Santos, Carvalho, Alves, & Pereira, 2012). Similarly, when the larvae sourced from all five hosts were switched to spinach, percent mortality due to all insecticides except cypermethrin decreased.…”
Section: Discussionmentioning
confidence: 99%